The Bibliometric Study of Flood Discharge by Unit Hydrograph Method Nakayasu Synthetic (HSS) and Soil Conservation Service (SCS) - Jenny Jenny; Andri Irfan Rifai; Jody Martin Ginting; Joewono Prasetijo (International Journal Labs, 2024)
Urban territorial expansion and forest disclosure are two examples of large-scale modifications necessary because of population growth and the rising demand for land. The paper analyzes the various facets of urban development and the essential role that hydrology plays in planning construction projects and water infrastructure. Hydrology study becomes essential for engineers designing and developing structures involving water resources, especially when flood conditions arise. The paper explores two commonly used flood hydrograph approaches, the Nakayasu Synthetic and the Soil Conservation Service (SCS) Unit Synthetic, concentrating on the design of flood discharge and its significance in flood management. The study provides insight into the feasibility of existing hydrograph techniques for determining flood discharge and is based on bibliometric data from earlier studies.